Concepts of Agrarian Law in Costa Rica - Ulate Chacón, Enrique Napoleón (Przegląd Prawa Rolnego, 2019)
This research aims to explain, in a concise manner, the origin and development of agricultural law in Costa Rica. For this purpose, the evolution of the agrarian normative system is analysed first, including its exceptional and specific norms, that existed before the consolidation of the constitutional agrarian law. It also addresses the notion of agricultural law as a legal science, according to modern doctrine, and the impact that Italian doctrine had on the concept of agricultural activity in Costa Rica. The most recent evolution is explained, related to policies and norms of territorial rural development, as well as the new competences granted by the Agrarian Procedural Code as of its entry into force in February 2020.